Metode multisensori untuk meningkatkan kemampuan membaca siswa kelas awal di SDN 1 Rubung Buyung - muhammad azam muttaqin, muhammad azam muttaqin; Muhammad Azam Muttaqin (MUJAHADA: Jurnal Pengabdian Masyarakat, 2023)
Indonesian subjects are very important subjects that are taught at all levels of education. It includes four skills that teachers must develop to their students. The four abilities are listening, speaking, reading, and writing. The ability to read is very important in this regard. The problem in the field is that students have low reading skills. On the basis of this problem, the study began. According to data collected from SDN 1 Rubung Buyung students, this study will use multisensory methods to improve their reading skills. This research uses the PAR research method, which is a type of research that involves the participation of community members in doing something or getting something desired.